Intracortical lipoma of the tibia - GC Bloemsma; MJ van Kints (Journal of the Belgian Society of Radiology, 2014)
Background: A 42-year-old female presented with chronic knee pain. Anamnesis and physical examination revealed no history of traumatic events. Furthermore, there was no local tenderness, swelling or warm aspect of the knees or tibiae. On conventional imaging, gonarthrosis was seen, as well as a well-defined diaphyseal osteolytic lesion. Further evaluation of the bone lesion was done by CT scan and MRI.